2010
DOI: 10.1186/1471-2458-10-157
|View full text |Cite
|
Sign up to set email alerts
|

Estimating attendance for breast cancer screening in ethnic groups in London

Abstract: BackgroundBreast screening uptake in London is below the Government's target of 70% and we investigate whether ethnicity affects this. Information on the ethnicity for the individual women invited is unavailable, so we use an area-based method similar to that routinely used to derive a geographical measure for socioeconomic deprivation.MethodsWe extracted 742,786 observations on attendance for routine appointments between 2004 and 2007 collected by the London Quality Assurance Reference Centre. Each woman was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 22 publications
8
58
0
1
Order By: Relevance
“…In our sample, the white and black ethnicities were slightly over-represented compared with the borough population in general, and Asian women were under-represented, especially in the 60+ years age group. This can be compared with the study by Renshaw et al [26] in which attendance at screening was found to be low for both black and Asian women. Our sample covered the age range invited to screening well: women aged between 47 and 73 are sent appointments, and our sample reported a range of 46-74 years, with an average age of 56 years; 26% of the sample was aged 60 years or over.…”
Section: Sample Demographicsmentioning
confidence: 83%
See 1 more Smart Citation
“…In our sample, the white and black ethnicities were slightly over-represented compared with the borough population in general, and Asian women were under-represented, especially in the 60+ years age group. This can be compared with the study by Renshaw et al [26] in which attendance at screening was found to be low for both black and Asian women. Our sample covered the age range invited to screening well: women aged between 47 and 73 are sent appointments, and our sample reported a range of 46-74 years, with an average age of 56 years; 26% of the sample was aged 60 years or over.…”
Section: Sample Demographicsmentioning
confidence: 83%
“…Similarly, details are routinely recorded about women diagnosed with BC [23] or those who have died as a result of the disease [24]. In addition, specific groups recognized as underrepresented in screening populations, such as ethnic minorities [25,26] or those who choose not to attend [27], are also of interest. However, only the recent PROCAS study has collected basic data about risk factors in a UK screening setting and used it to calculate risk levels [28].…”
Section: Risk Distributionmentioning
confidence: 99%
“…This has been mostly attributed to a combination of genetic factors causing more aggressive tumours in Black women and advanced stages of the disease before presentation [6]. Late stage at diagnosis advances higher mortality from breast cancer [7]. Further evidence also suggest that differences in exposure to available breast screening services contribute to existing ethnic variations in breast cancer outcomes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Black women are also known to develop breast cancer at a much younger age compared to their White counterparts [4,16]. Thus, early help seeking and stage at diagnosis have emerged as dominant predictors of breast cancer survival and can contribute significantly to reducing ethnic inequalities in breast cancer outcomes [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the ONS and in a study on breast cancer, reports at times contrast BME with "White British" and at other times contrasts BME with "White," which potentially includes non-British White groups (ONS 2003;Renshaw et al 2010). In speaking about her research project on BME groups, Bakare criticises the terminology "BME" as not being appropriate for "non-White groups," but then goes on to mention new ethnic communities in Britain, which in fact do include ethnic minorities commonly classified as White groups (most notably, Eastern European populations in the UK) (Bakare 2007).…”
Section: Bme and Msmmentioning
confidence: 99%